Furniture development framework for cultural conservation: a case study of Peranakan Chinese in Singapore - Huang, Wenhong; Abdul Rahman, Ahmad Rizal; Gill, Sarjit S.; Raja Ahmad Effendi, Raja Ahmad Azmeer (Multidisciplinary Digital Publishing Institute, 2024)
The Peranakan Chinese, formed through intermarriage between Chinese immigrants and Southeast Asian indigenous people, represent a unique example of cultural amalgamation. As modern society evolves, the conservation of their culture faces significant challenges, particularly in balancing heritage preservation with contemporary relevance. Addressing how Peranakan cultural products can meet the functional and emotional needs of modern audiences while achieving sustainable cultural development is a question worthy of in-depth exploration. This study uses the “SR” furniture series from Singapore’s “I” brand as a case study to examine how cultural products can integrate Peranakan heritage into modern life while promoting cultural conservation. Guided by affordance theory and thematic analysis, this research identifies four key strategies: (1) Cultural Integration and Expression; (2) Modern Innovation in Furniture Design; (3) Promotion and Sustainability; and (4) Social Engagement and Education. Based on these strategies, this study proposes a framework for cultural conservation in furniture development. This framework offers actionable strategies for designers, businesses, and policymakers to create products that meet both functional and emotional needs while fostering cultural conservation and adaptation in a globalized context.